The effects of music therapy on the pain response of premature neonates after venipuncture - Gacias-Ocampo, Leslie
The use of music therapy for the care of the premature neonates is relatively new and not much is known about its beneficial effects in minimizing the pain response experienced by neonates undergoing medical treatment. Recent studies, however, reveal associations between the use of music therapy and improved oxygenation, increased weight gain, decreased hospital stay and improved behavioral state among neonate infants. The present study attempted to determine the effectiveness of music therapy in modulating the pain response of neonates in terms of improved oxygenation, decreased heart rate acceleration, and lower pain scores. This study was a double-blind experimental design with randomization. A total of 40 premature neonates were included in the study; each was randomly assigned to either the experimental or the control group. The experimental group was exposed to classical instrumental music while the control group was exposed to pre-recorded background noise that simulated actual environmental sounds. The intervention delivered via headphones was initiated 30 minutes before a scheduled venipuncture and terminated 5 minutes after the procedure. The tool used was a modified version of the Premature Infant Pain Profie (PAT) referred to in the study as the Pain Assessment Tool. It was modified by the clinical investigator to suit the needs of the study. It is a pain scale that incorporates both physiologic (heart rate and oxygen satuation) and behavioral indicators of pain (facial expressions).